FACTOR THAT INFLUENCING CAPITAL EXPENDITURE: PERSPECTIVE PECKING ORDER AND MANAGERIAL HYPOTHESES - Synta Sutanto; Werner Ria Murhadi; Mudji Utami (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2017)
The objectives of this study are to observe the impact of internal cash flow, insider ownership, investment opportunity, investment opportunity and firm size on the capital expenditure in two different theories. Those theories are: (1) the pecking order hypotheses and (2) the managerial hypotheses, tested in Indonesian case. On the one hand, the pecking order hypotheses postulates that managers can choose the level of capital expenditure to maximize the wealth of current shareholders without considering insider ownership in the company. On the other hand, according to the managerial hypotheses, managers whose ownership proportions are small tend to use higher level of internal cash flows to finance the capital expenditure than that which would maximize the wealth of current shareholders. The data of this study is collected from 11 manufacture companies as listed in the Indonesian Stock Exchange. The result of this study shows that the internal cash flow, insider ownership, firm size and investment opportunity have positive impact on the capital expenditure. However, the impact of insider ownership and investment opportunity on the capital expenditure are not significant. Eventually, this study is disposed appropriate with the pecking order hypotheses.